The Front-Populaire government and non-intervention / from L'Espagne socialiste
The Front-Populaire Government and Non-intervention. "L'Espagne socialiste", edited by Jean Zyromski, publishes the following account of the reasons which led France to propose "non-intervention" in Spain. "The Cabinet met in council to consider the attitude to be adopted. M. Delbos presented, on the basis of despatches from his agents and the views of his representatives ( Herbette, Leger and their colleagues ) a review of the situation in Spain. "When he had finished, the greater part of the Ministers were filled with consternation. The honourable gramophone of the Quai d'Orsay had painted the situation of governmental Spain - though without drawing any conclusion - in the most dismal colours. It should not be forgotten that that was still at the beginning of August 1936, when the Republicans only needed arms in order to crush Franco within a few weeks. "M. Jean Zay asked to speak and put the following question: "If I have correctly understood the account of the Minister for Foreign Affairs, it follows from all the information obtained that the victory of Franco is certain and the defeat of the Republicans unavoidable?" "That is exactly the position", replied the honourable M. Delbos. "In these conditions", concluded M. Jean Zay, "however painful it may be to our feelings, there is only one attitude to be adopted, that of non-intervention in the affairs of Spain." "This opinion was accepted after a short debate, and it was in these circumstances that the blockade was instituted against Republican Spain, which had committed the double crime of being exposed to fascist aggression and of placing itself in an unfavourable position, in the eyes of the agents of M. Delbos! "To-day, when we have more exact information on the situation of the respective parties in Spain in August 1936, it is possible to estimate the deliberate duplicity of the agents of the Quai d'Orsay and the fatal blindness of the leaders of the Front Populaire. "We have proved it time and time again: official France has never ceased to play for the victory of Franco. Too many capitalists are interested in it, so that the apparatus of the bourgeois state which they control is bound to be entirely at the service of their vassal in Spain. "To-day the position of our Spanish comrades is far more delicate than it was fifteen months ago. And we are responsible for this. "But we, and we alone, are able to turn the balance decisively. We can still save Spain. But it is high time. "Are the workers of France going to continue longer to be made fool of by imbeciles and traitors? "The National Council will have to reply to this question on November 6th." 292/946/16b/36